Histology and Histochemistry of the Adrenal Gland African Giant Rat (Cricetomys gambianus, Waterhouse) - Olukole,Samuel Gbadebo (Sociedad Chilena de Anatomía, 2016)
The histology and histochemistry of the adrenal gland of the African giant rat, AGR (Cricetomys gambianus Waterhouse) was carried out using ten adult male rats with the knowledge of providing information which could be helpful in an improved knowledge of the structure and function of the gland. The adrenal gland of the African giant rat has a distinct cortex and medulla surrounded by a thin rim of capsule. The adrenal cortex has three zones which are basically the zona glomerulosa, zona fasiculata and zona reticularis with the absence of zona intermedia. The zona glomerulosa contains polyhedral cells which form irregular clusters or cords while the zona fasiculata had radial cells of cuboidal or polyhedral shape. The cells of zona reticularis are similar to those of the zona fasiculata and in addition contain small cells as irregular cords and clusters. The cells of the adrenal medulla are composed of irregular epithelioid cells arranged in rounded groups or short cords and are mostly columnar or polyhedral chromaffin cells which are separated by sinusoids. The adrenal capsule, cortex and medulla were Periodic Acid-Schiff-positive.The adrenal capsule and adrenal medulla was Masson Trichrome-positive unlike the zona fasiculata and zona reticularis. The adrenal capsule and zona glomerulosa were Verhoeff-positive unlike the other zones of the gland. In conclusion the histology of the adrenal gland of the AGR is similar to those of other mammals with a few exceptions, the entire gland is rich in carbohydrate while the capsule and by extension, the outermost portion of the cortex are rich in collagen and elastic fibers. The outcome of this research provides information needed in the better improved understanding of the structure and function of the adrenal gland of the animal.